Colonization of oak stumps by the oak pinhole borer in temperate forests and the efficacy of pheromone traps: Implications for pest management - Resnerová, Karolina; Šenfeldová, Soňa; Horák, Jakub; Popelková, Daniela; Holuša, Jaroslav (Frontiers in Forests and Global Change, 2023)
Introduction The present changes in climate and land use have led to an increase in pest population densities. The oak pinhole borer, Platypus cylindrus, is one of the ambrosia beetles, which are known to infect wood tissue with fungi from their mycangia. These fungi are responsible for cellulose degradation. This species is now responsible for more frequent timber damage throughout Europe. Therefore, it is assumed that there is a high risk of P. cylindrus outbreaks in the future with possible subsequent oak diebacks. We focused on (1) the influence of stump diameter on P. cylindrus attraction and abundance; (2) the trapping efficacy by a specific pheromone and the impact on nontarget arthropods; and (3) interannual changes in trap catches. Methods The research was performed from 2015–2017 with a postharvest survey of stumps. We further analyzed the catches of P. cylindrus and of nontarget arthropods on pheromone traps compared to ethanol-baited traps. Results and discussion In total, 12,504 adults were trapped during the 3 years of the study. P. cylindrus abundance was positively correlated with stump diameter and interannual changes. The type of compound used for trapping positively affected the trapping efficacy. However, the pheromone type did not have an impact on nontarget beetles. We consider oak stumps to be a reservoir the oak pinhole borer. Therefore, we recommend their debarking or removal, especially in the case of stumps with a larger diameter (over 61 cm).